An Adult Education Course on African Novels - Leyland, Peter (INSTED: Interdisciplinary Studies in Education & Society, 2023)
This study is about the importance of African authors in literature and the creation of an adult education course on African novels. It begins with my acknowledgement of a historian named David Olusoga and a novelist named Ben Okri. The first, Olusoga, produced a TV programme that gave me confidence that my idea for a course entitled African Novels could be successful. The second, Okri, wrote about how African Literature was the future. I will explain how I picked up their ideas and used them as a rationale for the course. The Workers’ Educational Association, for whom I produced the course, has a long history of student involvement. I have a great interest in both student autonomy and students taking part in their own learning. In my tutor role, I wanted African Novels to begin with a general idea about African authors and move to more specific books as the course proceeded. To this end, I began the course with an overview of the subject and a statement from the African novelist Chinua Achebe – to the effect that when you begin to identify with someone of a different colour and who even eats different food from you, then literature is really performing its wonders. I hoped that the students would carry out this identification. The paper will use auto/biographical methods, as defined in Merrill and West (2009, p. 5), to tell the story of how this course was created during a teaching space when my adult education centre was closed by the pandemic. The course could only be delivered once tutors and students could meet again face to face, and I give an example of this. The paper will be supported by reference to my own extensive research on bibliotherapy and by an account of how I used autoethnography as a research method. Both of these ideas enabled the course to develop and grow through reading, research, practice and reflection, as I will show.